Definitive Treatment of Open Pelvic Fractures with External Fixator - Ba, Papa Amadou; Ba, Abdoulaye; Djiba, Cherif Sadibou; Dembélé, Mamadou (International Journal of Innovative Research in Medical Science, 2023)
Background: Unstable and open pelvic fractures are often associated with significant morbidity and mortality, especially in patients with multiple injuries. Early pelvic fixation provides stability and should diminish ongoing hemorrhage. Materials and Methods: We undertook a retrospective and descriptive study of all cases of unstable open pelvic fractures treated with external fixators in the orthopedic and trauma surgery department of the Army Training Hospital Principal in Dakar over 4 years ranging from 1 January 2018 to 31 December 2022. Results: 12 patients were included in this study. The mean age of the patients was 39 years with extremes of 21 and 56 years. The series consisted of 10 men (83.3%) and 2 women (16.7%), representing a sex ratio of 5. The etiology of the open fractures was road traffic accidents (61%), followed by public road accidents (33%), and finally falls from a high place (6%). The injury mechanisms were direct impact in 9 cases and 3 cases of indirect impact by shearing. Bone injuries were Tile B in 75% and Tile C in 25%. Soft tissue lesions were located in the perineum in 7 patients, in the inguinal area in 2 patients, and the buttock in 1 patient. Pelvic exofixation was performed in all patients with an average delay of 12 hours, with extremes of 4 and 24 hours. One case of infection was observed in the medium-term outcome. Three deaths were recorded. Radiographically, the reduction was satisfactory in 75% of cases (N=9) (Figs. 6 and 7), tolerable in 16.7% (N=2), and poor in 8.3% (N=1). Two patients had a residual disjunction of more than 5mm. Conclusion: The external fixator in unstable open fractures of the pelvis appears to be a good alternative that finds its place within the limits of emergency internal osteosynthesis (hemodynamic instability, hemorrhagic and infectious risk). The limits of its use in isolation are related to its inefficiency in the reduction and correct stabilization of lesions of the posterior arch.